Design and synthesis study of the thermo-sensitive poly (N-vinylpyrrolidone-b- N, N-diethylacrylamide) - Xiayun Zhang; Zhongduo Yang; Dengmin Xie; Donglei Liu; Zhenbin Chen; Ke Li; Zhizhong Li; Brandon Tichnell; Zhen Liu (Designed Monomers and Polymers, 2018)
The reversible addition fragmentation chain transfer (RAFT) polymerization method was adopted here to prepare a series of thermo-sensitive copolymers, poly (N,N-diethyl- acrylamide-b-N-vinylpyrrolidone). Their structures, molecular weight distribution and temperature sensitivity performances were characterized by the nuclear magnetic resonance (1HNMR), the gel permeation chromatography (GPC) and the fluorescence spectrophotometer, respectively. It has been identified that the synthesis reaction of the block copolymer was living polymerization. The thermo-sensitivity study suggested that N-vinylpyrrolidone (NVP), played a key role on the lower critical solution temperature (LCST) performance.